STRATEGI INVESTASI JANGKA PANJANG: MEMILIH ANTARA INVESTASI RIIL DAN INVESTASI KEUANGAN - lita, lita; susilawati (Jurnal Ekonomi Bisnis Manajemen Prima, 2024)
This research aims to compare the performance of gold and stock investments, analyze the factors influencing investment decisions, and provide recommendations for optimal long-term investment strategies. The study employs interviews with an investor with over a decade of experience, actively investing in both gold and stocks, employing a qualitative-descriptive. The results indicate that gold has advantages in terms of stability and risk compared to stocks. Gold, as a safe haven asset, tends to maintain or increase its value during uncertain global economic and geopolitical conditions, providing significant protection against inflation and economic uncertainty. Conversely, stocks offer high capital growth potential but come with greater risk due to market volatility. In the long term, gold shows more stable and predictable returns, making it a more optimal choice for investors seeking to protect their wealth from value erosion due to inflation. Based on this analysis, it is recommended that investors diversify their portfolios by allocating a significant portion of assets into gold to reduce overall risk and provide long-term stability. Additionally, investors are advised to continuously monitor global economic conditions, consult financial experts, and focus on long-term gold investments to achieve their financial goals more effectively